Population structure of Lahille extquotesingles bottlenose dolphins (Tursiops truncatus gephyreus) using SNPs and stable isotopes of carbon and nitrogen, Patos Lagoon, Brazil - Rodrigo Genoves (PANGAEA, 2019)
This study is about common bottlenose dolphins. The SNPs data were used for population structure analysis using the fastSTRUCTURE and principal components analysis (PCA). For stable isotopes, Bayesian mixing models were used to investigate prey contribution and Stable Isotope Bayesian Ellipses to identify the isotopic niche in R.